Macroeconomic Factors, Foreign Portfolio Investment, Market Capitalization and Stock Return of Firms Listed at the Securities Exchanges in East Africa - Kimani Ngure, Francis (My University, 2022)
ABSTRACT Securities exchange play a vital role in the growth of an economy by encouraging savings and investment, as well as helping local and international investors to access cost-effective capital. Despite the benefits of the sector, investors are faced with high volatility of stock returns which poses greater risk to their investment. This study thus investigated the effect of macroeconomic factors, foreign portfolio investment and market capitalization on stock returns of firms listed in the East Africa Securities Exchanges. The study adopted arbitrage pricing theory, the neoclassical theory of investments and efficient market hypothesis. The study was guided by positivist research philosophy and longitudinal research design. The target population comprised of all the ninety-six listed companies in the Securities Exchanges in East Africa which have traded for five consecutive years as at 31st December 2020. The study used secondary data for five years ranging from 2016 to 2020. The study found that macroeconomic factors significantly affect stock returns. Specifically, foreign exchange rate negatively and significantly affects stock returns. Gross domestic product positively and significantly affects stock returns. Inflation rate negatively and significantly affects stock returns. Similarly, interest rate negatively and significantly affects stock returns. The study also found that macro-economic variables significantly affect foreign portfolio investment. Specifically, foreign exchange rate positively and significantly affects foreign portfolio investment. Gross domestic product on the other hand negatively and significantly affects foreign portfolio investments. Inflation rate negatively and significantly affects foreign portfolio investment. Interest rate positively and significantly affects foreign portfolio investment. The study also found that foreign portfolio investment positively and significantly affects stock returns and intervene the relationship between macroeconomic factors and stock returns. Market capitalization also significantly affect stock returns and moderates the relationship between macroeconomic factors and stock return. The study concluded that macroeconomic variables significantly affect stock returns. The study also concluded that foreign portfolio investment intervenes the relationship between macro-economic economic factors and stock returns. Similarly, market capitalisation positively and significantly affected stock performance of the listed firms and moderates the relationship between macroeconomic factors and stock returns. The study recommends that governments and other stakeholders should put in place macro prudential policies in order to encourage investments and boost stock returns. The regulators should come up with policies that will stabilize inflation, reduce or stabilize interest rates, stabilize or reduce exchange rates and also ensure growth in GDP. Directors of various firms and investors in the stock exchange should also scan the nature of macro environment and come up with strategies that will counter the negative effects and capitalise on the opportunities. The study suggested that future research may focus on data from other firms operating in different stock exchanges to compare and contrast the effect of macro prudential policies adopted in the various countries and its effects on foreign portfolio investment and stock returns.
Keywords: Macroeconomic Factors; Foreign Portfolio Investment; Market Capitalization